Influence of Temperature and Reaction Time on the Performance of Thermal Pyrolysis of Compact Polystyrene Waste. Issue 1 (April 2021) - Palmay, P; Nuñez, R; Donoso, C; Bruno, J
Abstract: The purpose of this study is to determine the influence of the temperature and reaction time on the thermal pyrolysis process of compact polystyrene residues based on the percentage of liquid obtained at a heating cup of 15 C min -1 and cooling system for the condensation of pyrolytic gases at 10 ° C. It worked with temperatures between 375 and 425 °C and times of 5 and 10 minutes. The results showed that the reaction time has no representative influence on the liquid fraction, while the temperature has a great importance in the liquid yield reaching a maximum contribution at 400 °C, after this the percentage of liquid oils tends to decrease by guiding the formation of the gas fraction. The maximum production was 81.4% with a kinematic viscosity of 1, 026 mm 2 s -1, relative density 0.9352, flash point 24 °C and a caloric power of 48.5 MJ kg -1 . The mixture of aromatic hydrocarbons obtained, with carbon chains between C6 and C20, are present in 75% by mass.